Tiny Green Army: Fighting Malaria with Plants and Nanotechnology - Isabelle Moraes-; Bianca P. T. de Moraes; Adriana R. Silva; Stela R. Ferrarini; Cassiano F. Gonçalves- (MDPI AG, 2024)
Malaria poses a global threat to human health, with millions of cases and thousands of deaths each year, mainly affecting developing countries in tropical and subtropical regions. Malaria's causative agent is Plasmodium species, generally transmitted in the hematophagous act of female Anopheles sp. mosquitoes. The main approaches to fighting malaria are eliminating the parasite through drug treatments and preventing transmission with vector control. However, vector and parasite resistance to current strategies set a challenge. In response to the loss of drug efficacy and the environmental impact of pesticides, the focus shifted to the search for biocompatible products that could be antimalarial. Plant derivatives have a millennial application in traditional medicine, including the treatment of malaria, and show toxic effects towards the parasite and the mosquito, aside from being accessible and affordable. Its disadvantage lies in the type of administration because green chemical compounds rapidly degrade. The nanoformulation of these compounds can improve bioavailability, solubility, and efficacy. Thus, the nanotechnology-based development of plant products represents a relevant tool in the fight against malaria. We aim to review the effects of nanoparticles synthesized with plant extracts on Anopheles and Plasmodium while outlining the nanotechnology green synthesis and current malaria prevention strategies.